YOLOv8과 ORB 알고리즘 이용한 원통형 약통의 식별 - 김대현(Dae-Hyun Kim); 최효현(Hyo Hyun Choi) (한국컴퓨터정보학회논문지, 2024)
본 논문은 영상에서 특정 원통형 약통을 식별할 수 있는 모델 이미지 생성 방식을 제시하고 데이터 수집에 대한 기술을 연구한다. 기존 연구들은 객체 인식과 특정 객체 식별이 분리되어 있어이미지 스티칭(image stitching) 자동화에 적용하기 어려웠으며, 좌표 기반 이미지 추출 방식이 이미지 스티칭 과정에서 객체 영역 외의 정보도 모델 이미지에 포함시키는 문제를 갖고 있었다. 이를 해결하기 위해 본 논문은 최근에 출시된 YOLOv8(You Only Look Once)의 세그멘테이션(segmentation)기법을 수직축 회전하는 약통 영상에 적용하고 특징점 매칭 알고리즘인 ORB (Oriented FAST and Rotated BRIEF)를 활용하여 모델 이미지 생성을 자동화하였다. 연구 결과, 세그멘테이션 기법을 적용할 경우 특정 약통 식별시 인식률이 향상되었으며 특징점 매칭 알고리즘으로 생성된 모델 이미지는 특정 악통을 정확하게 식별해 낼 수 있었다. This paper introduces a method for generating model images that can identify specific cylindrical medicine containers in videos and investigates data collection techniques. Previous research had separated object detection from specific object recognition, making it challenging to apply automated image stitching. A significant issue was that the coordinate-based object detection method included extraneous information from outside the object area during the image stitching process. To overcome these challenges, this study applies the newly released YOLOv8 (You Only Look Once) segmentation technique to vertically rotating pill bottles video and employs the ORB (Oriented FAST and Rotated BRIEF) feature matching algorithm to automate model image generation. The research findings demonstrate that applying segmentation techniques improves recognition accuracy when identifying specific pill bottles. The model images created with the feature matching algorithm could accurately identify the specific pill bottles. KCI Citation Count: 0